THE ROLE OF AN INTEGRATED EDUCATIONAL ENVIRONMENT IN FORMING PRESCHOOLERS' KEY COMPETENCES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article highlights the main condition for organizing development centers in the upbringing of preschool children, rather than receiving ready-made knowledge from a teacher, is to give the child the opportunity to choose activities in development centers, in which he can independently acquire knowledge about the world around him, develop skills and abilities, and give the child the opportunity to be curious, independent in search, and join the research process.